AgWise Forecast-Based Optimum Planting Date & and cultivar Advisory Framework - Louise Leroux; Ahmed, Jemal Seid; Mkuhlani, Siyabusa; Srivastava, Amit; Worku, Wuletawu Abera (2025)
AgWise is a modular decision-support framework that generates climate-informed agricultural advisories for smallholder farming systems. This module combines remote sensing, seasonal climate forecasts, and crop modeling to identify optimum planting windows, cultivar suitability, and climate-conditioned yield outlooks under current and forecast conditions. AgWise is a modular framework for generating climate-informed agricultural advisories, including optimum planting windows, cultivar suitability, and yield outlooks, using remote sensing, seasonal climate forecasts, and crop models.